THE EFFECT OF SPIRITUAL THERAPY INTERVENTION ON THE RISK MENTAL HEALTH DISORDERS AMONG FLOOD VICTIMS - Arwansyah Kirin, Arwansyah Kirin; Shakila Ahmad, Shakila Ahmad; Faisal Husen Ismail, Faisal Husen Ismail; Arifki Budia Warman, Arifki Budia Warman; Ramdan Baba, Ramdan Baba (RGSA, 2024)
Introduction: Disasters have diverse effects on various aspects of life, particularly on the psychological wellbeing of affected individuals. Victims of disasters often experience anxiety, trauma, stress, fear, and even prolonged sadness. For example, the flood disaster that occurred in Mukim Sri Medan, Batu Pahat, Johor, in 2023 is believed to have adversely affected the mental health of the affected community. Therefore, there is a need for strategies to address these mental health disruptions, and one potential approach is spiritual therapy. Objective: This research aims to assess the post-disaster mental health status of flood victims and analyze the influence of spiritual therapy on the mental health risk of flood victims in Mukim Sri Medan, Batu Pahat. Methods: This study adopts a quantitative approach using survey methods and questionnaires as research instruments. The target population includes individuals who were flood victims in Mukim Sri Medan, Batu Pahat. The sample consists of 207 respondents selected through non-probability sampling techniques, specifically accidental sampling. Data collection was conducted through a survey using questionnaires distributed to 207 respondents in the Mukim Sri Medan area. Data analysis employed multiple linear regression tests, correlation and determination coefficient tests, T-tests (partial), F-test (simultaneous), and descriptive analysis. Results and Conclusion: Research findings indicate that the majority of the post-flood mental health status of the community is high, with an overall mean score of 3.67. Spiritual therapy has a strong correlation with the postdisaster mental health of flood victims, with a significant value of 0.004b < 0.05, and a calculated t-value of 2.928 > t table 1.971, exerting an influence of 50.0%. Originality/Value: This study provides us with insights into the importance of maintaining inner strength in facing various disasters, especially floods, by engaging in therapy, whether it be mental therapy or spiritual therapy. Without therapy within oneself, the likelihood of mental health being affected, especially when confronted with the calamity of a disaster, is high. This is because disasters not only destroy physical objects but also impact mental health